PENDIDIKAN KRISTEN DI TAMAN KANAK-KANAK MELALUI METODE MONTESSORI - Wahyu Wijiati; Sari Dwi Kristianto (JURNAL PENABIBLOS, 2024)
Christian education in kindergarten is very important, because students of kindergarten are part of the golden age of human development. Therefore, proper teaching methods are needed for Christian education in kindergarten to be successful. The Montessory method is seen as an effective method for Christian education in Kindergarten. This study uses a descriptive qualitative approach through literature studies to delve deeply into the montessory method. In addition, the author also made observations in kindergartes to get the proper application of the montessory method in the implementation of Christian education. This is to explain in depth that Christian education in kindergarten through the Montessori method is very effective.